Correction to: 3-Triethylammonium propane sulfonate ionic liquids for Nafion-based composite membranes for PEM fuel cells - Zanchet, Letícia; da Trindade, Letícia Guerreiro [UNESP]; Bariviera, William; Nobre Borba, Katiúscia M.; Santos, Rapher Donizete Moreira; Paganin, Valdecir Antonio; de Oliveira, Cristiane Pontes; Ticianelli, Edson Antonio; Martini, Emilse Maria Agostini; de Souza, Michèle Oberson (Springer Nature, 2020)
After the manuscript was revised following peer review, an error was introduced in the conductivity data reported in Table 3. Adding the standard values (SD) of the original values, which were correct, we made an error about the unit used for the membrane thickness. Consequently, all the published conductivity values and their standard deviation (SD) need to be multiplied by 10-1. Below is Table 3 with the corrected values as well as their SD. (Figure presented.).
Correction to: 3-Triethylammonium propane sulfonate ionic liquids for Nafion-based composite membranes for PEM fuel cells (Journal of Materials Science, (2020), 55, 16, (6928-6941), 10.1007/s10853-020-04454-4)